BIOLOGICAL STUDIES ON THE ANCHOVY, THRYSSA GAUTAMIENSIS BABU RAO (PISCES: ENGRAULIDAE) - Rao, M. Babu (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
Biology of the anchovy, Thryssa gautamiensis BABU RAO, which forms a fishery in the Godavari estuary (East Coast of India) was studied for the three seasons, i.e. 1959-60, 1960-61 and 196162. The population pattern was studied during the three seasons by means of montly percentage length frequency curves and fitting normal curves. Length weight studies were made for the three seasons, the best fit equations to express the relationship have been calculated and differences of relationships within seasons have been tested. Relative condition ('Kn') variation studies have been made for the different length groups of the fish for the two sexes. The variations of fecundity in relation to length and weight of fish respectively were studied and the equation to express their relationships have been established. The spawning season and the sizes, of ova at different stages of maturity have been determined by means of ova diameter measurement studies. The food preferences of this species have been ascertained by studying the gut contents and their item wise percentage frequencies in different months.